Prevalence and predictors of malaria in pregnant women in Sub-Saharan Africa: a systematic review and meta-analysis - Tembo, Innocent; Kalele, Jane C.; Simwinga, Bright; Mgemezulu, Towela; Mwanza, Teembo; Kazonga, Eustarckio; Mudenda, Steward; Mutemwa, Richard (International Journal Of Community Medicine And Public Health, 2024)
Malaria remains a significant threat to pregnant women in sub-Saharan Africa. This systematic review and meta-analysis aims to estimate the prevalence and identify predictors of malaria infection among pregnant women in the region. Following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a comprehensive search of PubMed Central, Google Scholar, EMBASE, ScienceDirect, and Cochrane Library was conducted, including 15 studies published between 2013 and 2023. The pooled prevalence of malaria, calculated using a random-effects model, was 19.0% (95% CI: 0.13-0.26), with heterogeneity (I²=81.9%) reflecting geographical and climatic diversity. Prevalence rates ranged from 6.4% in Burkina Faso to 36.4% in Tanzania. Asymptomatic cases had a prevalence of 19.0% (95% CI: 0.10-0.38), while symptomatic cases were slightly lower at 17.0% (95% CI: 0.12-0.23). Predictors of malaria included maternal age, parity, insecticide-treated net usage, intermittent preventive treatment, trimester-specific risk, and education level. These findings underscore the need for targeted, context-specific interventions to mitigate malaria risk among pregnant women in sub-Saharan Africa and inform effective malaria control strategies.